The Middle-upper Devonian clastic wedge of the Franklinian geosyncline ... - Embry, Ashton F. Ashton Fox (University of Calgary, 1976)
Bibliography: p. 259-274. ... : Middle - Upper Devonian elastic strata in the Canadian Arctic Islands are present over an area of about 200,000 sq km (75,000 sq miles) and are up to 5000 m (16,000 1) thick. The strata comprise a elastic wedge which was deposited in the Franklinian geosyncline prior to Late Devonian - Early Mississippian deformation. The elastic wedge is divided into eleven formations, and six facies are recognized within the strata. The formations and their facies content are: Blackley (submarine fan); Cape de Bray (marine slope); Weatherall (deltaic-marine shelf); Bird Fiord (open marine shelf and deltaic-marine shelf); Strathcona Fiord (meandering stream); Hecla Bay (braided stream); Fram (meandering stream); Hell Gate {braided stream); Nordstrand Point (meandering stream); Beverley Inlet (meandering stream); and Parry Islands (braided stream, meandering stream and deltaic-marine shelf). Mineralogy, facies distributions, paleocurrent patterns and regional geology all indicate that the source areas of the elastic strata ...